Ceramic materials in dentistry: historical evolution and current practice - Kelly, J. R.; Benetti, P. [UNESP] (Wiley-Blackwell, 2011)
Dental ceramics are presented within a simplifying framework allowing for facile understanding of their development, composition and indications. Engineering assessments of clinical function are dealt with and literature is reviewed on the clinical behaviour of all-ceramic systems. Practical aspects are presented regarding the choice and use of dental ceramics to maximize aesthetics and durability, emphasizing what we know and how we know it.
Keywords: Ceramics; particle-filled glasses; polycrystalline ceramics; CAD; CAM; all-ceramic restorations